Uncovering Tax Avoidance at Government Agencies: A Phenomenological Research - Riskiyadi, Moh; Tarjo, Tarjo; Anggono, Alexander (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022)DO - 10.24843/JIAB.2022.v17.i01.p02, 2021)
Interpreting tax avoidance as tax fraud is a very interesting discussion because it depends on the point of view of how to react. This research aims to reveal the essence of tax avoidance on financial management in a government agency. This research used a qualitative method with a transcendental phenomenological approach in a government agency of a district in the Madura region with informants from the parties involved in financial management and supplier partners, and data collection was carried out by interview, observation, and documentation. The research findings reveal the essence of financial management compulsion to do tax evasion compared to committing fraud on state or regional finances managed by a government agency. It is hoped that this research will be able to provide a different perspective regarding the dilemma in financial management in government agencies so that regulations and policies on state or regional financial management can be addressed. Keywords: fraud, tax avoidance, tax evasion, government agencies